Diagnosis and management of depression - Hanwella, Raveen; De Silva, Varuni (Ceylon Medical Journal, 2008)
Depression is a disabling illness which decreases quality of life and productivity. The point prevalence of major depression ranges from 5% to 9% among adults in primary care settings. Both pharmacological and psychological treatment are effective in treating depression.
Keywords: depression; antidepressants; continuing medical education; diagnosis; management